A Protective Mechanism of Glucogon-like Peptide-1 on AGEs-Induced H9C2 Cardiomyocytes Injury through Inhibiting ROS-Autophagy Pathway - Gu, Xiang; Zhang, Jun; Xia, Wen-Jing; Zhang, Pu-Hua; Yin, Chang-Chang; Guana, Gao-Peng; Long, Huang (Cardiology and Cardiovascular Medicine, 2017)
Diabetic cardiomyopathy is involved in multiple molecular mechanisms, including advanced glycosylation end products (AGEs), reactive oxygen species (ROS), and autophagy. Glucogon-like peptide-1 (GLP-1) is thought to prevent from the deleterious effects of AGEs through suppressing ROS in diabetes, but the role of GLP-1 in ROSmediated cardiomyocytes injury is unknown. In this study, we tested the hypothesis that Glucogon-like peptide-1 (GLP-1) would attenuate AGEs-induced injury in H9C2 cardiomyocytes by inhibiting ROS-autophagy pathway. Cultured H9C2 cardiomyocytes were treated with one of the following: (1) 1mg/L BSA , (2) 100mg/L AGEs-BSA, (3) 100mg/L AGEs-BSA and 10nmol/L GLP-1, (4) 100mg/L AGEs-BSA and 5nmol/L N-acetyl-L-Cysteine (antioxidant), (5) 100mg/L AGEs-BSA, 10nmol/L GLP-1 and 5μmol/L Rapamycin (autophagy agonist) for 24- hours. We found that AGEs impaired cell viability, increased Intracellular ROS productions, induced apoptosis and triggered autophagy; however, which were reversed remarkably by GLP-1or N-acetyl-L-Cysteine. Furthermore, the effects of GLP-1 of AGEs-induced cell injury were inhibited by Rapamycin except for ROS. These results suggest that GLP-1 may prevent H9C2 cardiomyocytes from AGEs-induced injury partly through inhibiting ROS-autophagy pathway.